Cover Feature: Robust, Scalable Synthesis of the Bulky Hagfeldt Donor for Dye‐Sensitized Solar Cells (ChemSusChem 2/2020). Issue 2 (20th January 2020) - Baumann, Alexandra; Watson, Jonathon; Delcamp, Jared H.
Abstract : The Cover Feature shows an umbrella representing the Hagfeldt donor. This molecule is commonly described as providing an "umbrella" effect in dye‐sensitized solar cells to stop the oxidation of reduced TiO2 by reagents in the electrolyte. The green grass represents the TiO2 surface, the umbrella represents the dye, and the dark rain portion of the sky represents the solar cell electrolyte with oxidizing agents being the rain or yellow spheres. The umbrella (or dye) is shielding electrons at the TiO2 surface from these oxidizing reagents. More information can be found in the Communication by A. Baumann et al. on page 283 in Issue 2, 2020 (DOI: 10.1002/cssc.201902349 ).